Antonio Cornejo Polar And The World Republic Of Letters - Westphalen Rodríguez, Yolanda (2019)
The article analyze the categories of contradictory totality and heterogeneity developed by Antonio Cornejo Polar, as well as other postulated categories from the Latin American sphere, to try to understand the dynamics of the globalization of the literary system, not as a linear process of homogenization,but as a process characterized by transculturation, multilingualism, multiculturalism, hybridity and heterogeneity, multiple reality crossed by complex ideological and intercultural conflicts, that is, not only by the coexistence in diversity, but by the conflictive character of this process. It also questions Franco Moretti’s concept of “world-system”, and Pascale Casanova’s approach to the World Republic of Letters, considering that both approaches fail to break with a perspective of Eurocentric analysis.